Improving A2-Level German Syntax And Morphology Via Learningapps.Org: a Web-Based Approach - Herlina Jasa Putri Harahap (Jurnal Pendidikan dan Pengajaran, 2024)
The rapid change of times made foreign languages necessary in the era of the Industrial Revolution 4.0, including German, which is taught in formal education. German language learning faces challenges due to the difference in grammatical systems between German (inflectional language) and Indonesian (agglutinative language). This difficulty often causes boredom and a lack of enthusiasm for learning. This research aims to create an A2-level German language learning media through Learning app. org-based quizzes. This development study uses the educational design research (EDR) method. The subjects involved in this research are one material expert and one media expert. The data collection methods used were interviews, observations, and questionnaires, and the instrument used was a questionnaire sheet. After the data was collected, it was analyzed using descriptive qualitative and quantitative data analysis methods. The results showed that based on validation data provided by material and media experts, the material achieved a validation score of 90%. This indicates that the material is suitable for learning media and falls into the Very Good category. In addition, the validation conducted by Learningapp.org resulted in a final percentage of 92.85%, confirming that Learningapp.org media is suitable for use in the Very Good category. So, Learningapp.org media is ideal for use. This research is expected to help learners expand morphology, building sentences, and improve syntactic understanding interactively.